Summary and prospect of body donation programs in Beijing in the past 20 years - ZHANG Han-lin, TANG Ke-yun, HU Xin-zhi, ZHANG Qing, WANG Nai-li, ZHANG Di, MA Chao (Jichu yixue yu linchuang, 2021)
Cadavers are essential to anatomical dissection courses. The body donation program is the primary source of cadavers used in the courses. In 1999, three body donation programs were founded in Peking Union Medical College, Capital Medical University, and Peking University Health Science Center, which opened a new era for body donation in Beijing. This article summarizes and prospects the body donation programs in Beijing in the past 20 years, and provides a reference for the operation and development of body donation in China.